Information and communication technologies for development in Africa. - Thioune, Ramata Molo (International Development Research Centre ; Council for the Development of Social Science Research in Africa, 2003)
This volume looks at the introduction, adoption, and utilization of ICTs at the community level. In various contexts - geographical, technological, socioeconomic, cultural, and institutional - the book explores the questions of community participation. It looks at how communities in sub-Saharan Africa have reacted to the changes brought about by the introduction of these new ICTs and, in detail, presents both the opportunities and the challenges that ICTs present for community development.